Pengaruh Efektivitas Pemungutan Pajak Hotel dan Kepatuhan Wajib Pajak terhadap Pelunasan Pajak Daerah - Nelsi Wisna (Jurnal Akuntansi)
The purpose of this research is to know and analyze the influence of tax collection effectivity and taxpayer compliance on local tax paid. By using the descriptive method, this research surveyed at 8 kinds of hotel in Bandung Town. The questionnaire was used as the research instrument supported by interview and documentation, and had been data collected from june 2007 until july 2007. Data analysis to test the hypothesis is multiple regression analysis by exercising software SPSS.